State of Knowledge of the Entomofauna of Some Resinous Species of the Traras Mountains (North West Algeria) - Nichane Mohamed (Contemporary Research and Perspectives in Biological Science Vol. 10, 2025)
As part of the biocenotic study of insects related to coniferous species in the Western Traras region (Tlemcen), as complete a knowledge as possible of the entomofauna frequenting, in particular, the Aleppo pine (Pinus halepensis Mill), the barabary Thuja (Tetraclinis articulata (Vahl) Master) and green Cypress (Cupressus sempervirens L.) are essential. The entomological inventory was carried out from 2020 until 2023, three years of study.The different methods of capturing insects (collecting leafy branches, collecting cones, sight hunting, sweep net, Japanese umbrella, bark stripping, aerial trap, Barber trap, yellow bin) have allowed us to collect a significant number of species, and a large number remain unknown. These species are divided into 10 systematic orders, the most important of which are Coleoptera, Hymenoptera and Lepidoptera. Through this list of insects and according to their feeding habits, we have discerned 6 diets to which these species belong. The most representative are defoliators, auxiliaries and xylophages. This inventory allowed us to draw up a list of insects harmful to the coniferous species studied in the region. They total 30 species including 9 defoliators, 8 xylophagous, 7 conobiantes, 5 Opophagous and 1 gall-eating species. The auxiliaries are represented by 26 species.